La ninfa de Aby Warburg : la mujer pájaro desde una posición deconstruccionista (2019)
"The psychohistorian of art, Aby Warburg (1866-1929), studied culture through its discomforts that are revealed in the repetitive gestures of different characters. Among them is the Nymph, who in every one of the scenes interrupts with her explosive entrances. The Nymphs that Warburg collected in his project Atlas Mnemosyne from the series on John the Baptist's life by Domenico Ghirlandaio are the harbinger of the beheading of John by a woman. With it, the voice of God the Father was incarnated in his throat. The Nymphs in Ghirlandaio's series are discomforts of a "disease": the end of patriarchy. In this essay, I will speak of a symbolic and recurring character that Warburg called the Nymph, who, like a bird woman, disordered and turned the work of the psychohistorian upside down with her flight. In this character, I see the harbinger of the moment of crisis of the patriarchy in the 21st century." -- Tomado del formato de documento de grado.